SINUS FLOOR AUGMENTATION WITH BONE BLOCK GRAFTING AND SIMULTANEOUS IMPLANT PLACEMENT. - George S. Manev; Christina Popova (Peytchinski Publishing, 2013)
Placement of dental implants in the posterior maxillary edentulous areas is often compromised by the limited volume of bone due to the anatomy of the maxillary sinuses. In such cases, the technique of Sinus Lift is indicated to provide a sufficient volume of hard tissue in order to achieve primary stability at implant placement. Simultaneous augmentation of the sinus floor and implant placement is severely limited by the amount of residual bone of the floor of the sinus.A clinical case of minimal residual bone at the bottom of the sinus is demonstrated. A sinus floor augmentation with bone block harvested from the mandibular symphysis is performed. The bone block is placed in the sinus after membrane elevation and fixed with a screw to the sinus floor. After fixation of the bone block in the sinus implant (10/4.1 mm TSV (Zimmer)) is placed in reconstructed bone with good primary stability. Healing occurs without complications and the third month X-ray showed normal density of bone around the implant. The technique is very sensitive to surgeon's skills.